PERAN KEPEMIMPINAN KEPALA SKOLAH DALAM IMPLEMENTASI MANAJEMEN MUTU TERPADU (MMT) DI MI AR-RAHMAN SAMARINDA - Alya Kamilin; Irfan Aziz; Suhartini; Suratman (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
This study aims to analyze the role of the madrasah principal’s leadership in implementing Total Quality Management (TQM) at MI Ar-Rahman Samarinda. The research is motivated by the suboptimal implementation of quality management systems, which has not significantly improved learning quality in madrasahs. This study employs a qualitative approach using observation and interviews with the principal, teachers, and students. Data were analyzed through data reduction, categorization, and thematic interpretation. The findings reveal that the principal plays multiple roles as an initiator, facilitator, motivator, and evaluator in implementing TQM. These roles contribute to improved discipline, better educational service organization, and strengthened religious culture within the madrasah. However, academic quality improvement remains limited due to the insufficient use of data-based evaluation. The study concludes that Islamic-based transformational leadership is essential for the successful implementation of TQM in madrasahs